design Of a Body Temperature Regulation System - Hroub, Wejdan; Sweity, Amani; Najjar, Alaa (جامعة بوليتكنك فلسطين - اجهزة طبية, 2013)
This project provides a new system to regulate the temperature of the patient, this system is based on the patients temperature regulation through the bed mattress by pumping water with appropriate temperature , the natural patients temperature is used as a reference to the system and being without any medical intervention. If body temperature less than the reference , the system will send a signal to the heating unit through PIC , which heats the water and then the pump pumps the heated water to the mattress through a special set of tubes. If the patients body temperature greater than the reference, the system will send a signal to the cooling unit and pump through PIC , which cools the water and pumps it to the mattress.
no of pages 53 , 26422, اجهزة طبية 2/2013, in the store
Keywords: a Body Temperature Regulation Systems